Criminal Aspects of Corruption Regarding Control of Regional Assets by Foundation X For Commercial Purposes - Asep Sapsudin; Asmaidar Asmaidar; Mohamad Dindin Hamam Sidik (Trunojoyo Madura University, 2025)
This study examines the criminal aspects of corruption in the control of Regional Government-Owned Assets (BMD) by Foundation X over the land formerly occupied by the Bandung Zoo. The research problem focuses on how the use of regional assets by a foundation for commercial purposes can be classified as a criminal act of corruption and how the law should be enforced. The foundation unlawfully managed and leased the land owned by the Bandung City Government without any formal agreement and failed to deposit the rental income into the regional treasury. This study employs a normative legal research method using a juridical-normative approach. The findings indicate that the actions in question fulfill the elements of a corruption offense: unlawful conduct, enrichment of oneself or others, and financial loss to the state, as stipulated in Articles 2 and 3 of the Anti-Corruption Law. Legal enforcement through criminal prosecution, restitution, asset confiscation, and regulatory harmonization between the Foundation Law and BMD management regulations are crucial steps to prevent the recurrence of public asset misuse. Formulating stricter regulations and strengthening oversight mechanisms in regional asset governance.Keywords: Corruption Crimes; Foundations law; Law Enforcement; Regional Assets;